2021
DOI: 10.1021/acsomega.1c04896
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Persulfate for Improved Naproxen Degradation Using FeCo2O4@g-C3N4 Heterojunction Photocatalysts

Abstract: An effective heterojunction with robust charge separation and enormous degradation efficiency is the major task for photocatalyst preparation. In this study, we have prepared the FeCo 2 O 4 -loaded g-C 3 N 4 nanosheet by the sol–gel-assisted calcination method for photo-Fenton-like degradation under visible-light irradiation by activating persulfate. The nanocomposite exhibits a higher charge separation efficiency than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Therefore, the accumulated CB electrons at g-C 3 N 4 and holes at VB of Bi 2 O 3 generate the superoxide radicals and hydroxyl radicals for the degradation reaction. This element of the Z-scheme mechanism is well matched with the scavengers' experiment and the literature reports [23][24][25][26]. The possible charge transport and degradation mechanism of the Bi 2 O 3 /g-C 3 N 4 nanocomposite is given below [1][2][3][4]:…”
Section: Evaluation Of Photocatalytic Activitysupporting
confidence: 81%
“…Therefore, the accumulated CB electrons at g-C 3 N 4 and holes at VB of Bi 2 O 3 generate the superoxide radicals and hydroxyl radicals for the degradation reaction. This element of the Z-scheme mechanism is well matched with the scavengers' experiment and the literature reports [23][24][25][26]. The possible charge transport and degradation mechanism of the Bi 2 O 3 /g-C 3 N 4 nanocomposite is given below [1][2][3][4]:…”
Section: Evaluation Of Photocatalytic Activitysupporting
confidence: 81%
“…Previous literature showed that the initial pH value of the suspension plays a significant role in organic photocatalytic degradation. 25,26 Therefore, a series of degradation experiments were carried out by setting the pH value of the suspension between 7.0 and 10.0 to prevent the dissolution of LDH at other pH values. The results are shown in Fig.…”
Section: Condition Optimizationmentioning
confidence: 99%
“…[9][10][11] Using g-C 3 N 4 as the PS/PMS heterogeneous activator can effectively avoid the above problems. [12,13] g-C 3 N 4 prepared by direct thermal polycondensation of nitrogen-containing precursors generally presents bulk particles with a small specific surface area and low photocarrier separation efficiency, [14,15] resulting in a poor activation effect on PMS. Semiconductor materials can effectively improve the efficiency of charge separation and transmission by constructing an internal electric field in the heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…Graphite carbon nitride (g‐C 3 N 4 ) is a visible light‐driven nonmetallic material with excellent chemical and thermal stability that can be prepared by a simple pyrolysis method with low cost and easily controlled structure and performance [9–11] . Using g‐C 3 N 4 as the PS/PMS heterogeneous activator can effectively avoid the above problems [12,13] …”
Section: Introductionmentioning
confidence: 99%